2018
DOI: 10.1111/jse.12301
|View full text |Cite
|
Sign up to set email alerts
|

Differences between the floras of the North and South Moluccas (Indonesia)

Abstract: The north and south Moluccas (Indonesia) have very different geotectonic origins and, due to that, a difference in flora is to be expected. The north Moluccas moved westwards along the north coast of New Guinea to their present position, the south Moluccas moved north from Australia. On the other hand, a comparable climate in both areas and (partial) submergence during tectonic movement may have equalized both floras. Collection data from Naturalis Biodiversity Center on 1559 species in 121 families treated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Zhao et al () and Rutgrink et al () focus on taxa in Malesia. In their biogeographic analysis of Prunus subgenus Laurocerasus section Mesopygeum , Zhao et al () found that the Wallace Line is an important line of demarcation for the two major clades within the section.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Zhao et al () and Rutgrink et al () focus on taxa in Malesia. In their biogeographic analysis of Prunus subgenus Laurocerasus section Mesopygeum , Zhao et al () found that the Wallace Line is an important line of demarcation for the two major clades within the section.…”
mentioning
confidence: 89%
“…This special issue includes works presented at this symposium, but also contains studies from the Australasian region, which neighbors the Pacific region and in many cases serves as the source area for Pacific oceanic island colonization. This issue comprises works that aim to reconstruct patterns throughout the entire Pacific (Appelhans et al, ) or that focus on islands groups in the Pacific (Paetzold et al, ; Price & Wagner, ) or parts of Australasia (Miller et al, ; Rutgrink et al, ; Zhao et al, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…General evidence of archaeological findings in North Maluku are older than the archaeological findings in the Southern Maluku Islands. Based on estimates of the oldest archaeological remains, geographically, the cultural time character of the Southern Maluku Islands were also generally separated from the Aru Islands area (Rutgrink, Visser, & van Welzen, 2018). Aru Islands is integrated into the Sahul Shelf, especially during the Last Glacial Maximum and also separated from the Southwest Maluku Region, which includes Wetar Island, Timor Island, Kisar Island, Leti Islands, to Babar Islands (O'Connell & Allen, 2007;Ray & Adams, 2001;Roberts et al, 2020;Sathiamurthy & Voris, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the checklists of the Malesian Euphorbiaceae (Airy Shaw, 1982; van Welzen, 2017) shows that 8 of the 81 recorded Moluccan species (in 26 genera) are endemic. The Moluccas are often treated as a monolithic biogeographic unit (i.e., same climate), but recently it was shown that the very different tectonic origins of North and South Moluccas warrant the recognition of two biogeographic provinces (Rutgrink et al, 2018).…”
Section: Introductionmentioning
confidence: 99%